Pengetahuan dan sikap ibu tentang penanganan diare pada balita - Ganda Sigalingging; Magdalena Ginting; Darwin Tamba; Jusniar Sianipar (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Children's growth and development can be hampered due to the adverse effects of diarrhea. If diarrhea is not treated properly, it can even lead to death. Lack of personal and environmental hygiene is a trigger factor for diarrhea. The incidence of diarrhea in infants aged 1 month to 1 year was 31.4% and infants aged five years was 25.2%. In Indonesia, the number 1 cause of infant death is caused by vomiting diarrhea. Purpose: To describe the knowledge and attitude of mothers about handling diarrhea in toddlers. Method: Descriptive research, with a population of all mothers who have children under five. The sampling technique used in this study was accidental sampling of 30 people. Data collection was done by interview using a questionnaire. Data analysis using univariate analysis. Results: Based on the results of the study of Maternal Knowledge and Attitudes About Handling Diarrhea in Toddlers at Puskesmas Lumut Tapanuli Tengah, it can be concluded that the majority of mothers' knowledge is sufficient as many as 17 people (56.7%) and a positive attitude as many as 22 people (73.3%). Conclusion: based on the results of this study there are still mothers who have insufficient knowledge, with a negative attitude, so that health counseling efforts are needed about diarrhea and how to prevent it and the importance of parents maintaining personal hygiene and the environment as well as baby food handlers always pay attention to hand hygiene and eating and drinking utensils used by babies.